The relationships between critical thinking skills and dispositions of generic nursing students and registered nurses enrolled in a Bachelor of Science in Nursing program. - Doas MD (Relationships Between Critical Thinking Skills & Dispositions of Generic Nursing Students & Registered Nurses Enrolled in a Bachelor of Science in Nursing Program, 1996)
The purpose of this study was to determine if there were any significant correlations among freshman generic, senior generic, RN-BSN first year, and RN-BSN senior year nursing students in levels of critical thinking skills and critical thinking dispositions. This study examined the relationships between a variety of demographic variables and critical thinking skills and critical thinking dispositions. The demographic variables included: age, gender, marital status, years of professional nursing experience, membership in professional/student organizations, number of formal critical thinking courses taken, and other earned degrees.Two instruments were used in this study. They induced the California Critical Thinking Skills Test (CCTST) and the California Critical Thinking Dispositions Inventory (CCTDI). Data analysis was primarily completed using one-way analysis of variance. The sample consisted of 213 nursing students at one university with two branch campuses in Western Pennsylvania. The dependent variables of Truth-Seeking, Open-Mindedness, Analyticity, Systematicity, Confidence, Inquisitiveness, Maturity and Critical Thinking Dispositions Total were evaluated for differences between levels of class. The effect of specific types of nursing programs, educational experience, and selected demographic variables were evaluated by examining the differences by level of class on the critical thinking skills of Analysis, Evaluation, Inference, Dedutive Reasoning, and Inductive Reasoning.There were significant differences between the levels of class and specific critical thinking dispositions. There were no significant differences between the levels of class and the critical thinking skills.Implications for nursing education and practice suggest that educators examine a variety of teaching strategies and activities that could cultivate critical thinking skills.